Nyai Ontosoroh's Resilience Reflected In Pramoedya Ananta Toer's Novel "This Earth Of Mankind" (1975): An Individual Psychological Approach - Utami, Mimin Yudha; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
The major issue of this study is; how resilience of Nyai Ontosoroh is reflected in Pramoedya Ananta Toer in This Earth of Mankind novel (1975). The objective of this study is to analyze the structural element This Earth of Mankind novel (1975) and to analyze the major character of Nyai Ontosoroh's resilience based on Individual psychological Approach. This research is qualitative study. The data sources consists of primary data source and secondary data source. The primary data source is This Earth of Mankind novel itself and the secondary data sources are taken from other sources, they are books, virtual references as documentation, and internet. The data analysis in this research is descriptive qualitative analysis. The results of the study shows; the resilience of Nyai Ontosoroh become a native honoured; first nyai tried for her life more better with the personality of person who likes learning a new thing and a person who likes to work hard although she just a concubine. The second, She wants to save herself from her life as a concubine become a Native honoured and she was tried to do was defend her daughter, Annelis. Which, her daughter will take in to Nederlands.